Why Are You So Thin? Exploring Individual and Household Level Factors of Adolescent Girls' Food Consumption in Rural Bauchi, Northern Nigeria. (7th June 2021) - Sosanya, Mercy; Freeland-Graves, Jeanne; Gbemileke, Ayodele; Adesanya, Dorothy; Samuel, Folake
Abstract: Objectives: Bauchi State has the second highest prevalence of acute malnutrition (13%) among girls and women in Nigeria. Individual and household-level factors that may influence the food consumption of rural adolescent girls were explored in six local government areas of Bauchi State in Northern Nigeria. Methods: Focus group discussions were used to collect data from unmarried girls (11–16 years). Each of the six discussions had eight participants. Discussions were conducted in the Hausa language, tape recorded by skilled interviewers, transcribed, translated into English and analyzed using thematic analysis. Results: Emerging themes from this study included age at marriage, knowledge of basic nutrition concepts, foods perceived as nourishing for girls and women, food preferences of adolescent girls, and gender inequities in household access to food. Intended and actual ages at marriage overlapped significantly and ranged from 13–20 years. The concern about not finding a husband after a certain age, and a desire to be independent of parents were common reasons for early marriage. The knowledge of basic concepts in nutrition including types of nutrients and food groups was minimal. When asked what foods were perceived to be nourishing for women and girls, participants mentioned cereals mostly, a few plant and animal protein foods, but also ultra-processed foods and drinks. In order of taste preference, adolescent girls chose cereal foods, ultra-processed foods, animal source foods, legumes, tubers and vegetables. Rice and pasta were the most preferred food items, while fruit and dairy products were not mentioned. Prevailing limited access to animal source foods was attributed to large household size and financial constraints. All participants reported receiving smaller food portions than their adolescent male siblings. Perceived reasons for this disparity include the contribution of boys to farm labor and household income, gender stereotypes ("just because they are boys"), and their larger body frames and appetites. Some believed that boys needed more food for energy in order to impregnate girls. Conclusions: Early marriage, poor nutrition knowledge and disparities in access to food may influence food consumption and, thus, contribute to poor nutritional status in adolescent girls in Bauchi State. Funding Sources: Oxfam LINE Project, Bauchi funded the study.